Sustainable Catching-Up Requires a Complete Turn in Competitiveness - Baksay, Gergely; Nagy, Ágnes (Public Finance Quarterly, 2022)
Further strengthening of competitiveness is essential for Hungary’s sustainable growth and catching up. According to the Magyar Nemzeti Bank’s approach, an economy is competitive if it utilises its available resources optimally to attain the highest possible, but at the same time sustainable, level of welfare. In the past decade, the macroeconomic conditions necessary for a turn in competitiveness have developed in Hungary, which also provided a stable basis for managing the economic impact of the coronavirus pandemic. Hungary was ranked 18th in the MNB’s competitiveness ranking among the 27 countries of the European Union in 2021. The result shows that further strengthening competitiveness and the effective release of growth reserves, in particular in the areas of high-quality human capital and the digital and green transition of the economy, are essential to achieve sustainable catching-up and avoid the middle-income trap.